Studi Kasus:Penerapan Terapi Spiritual Emotional Freedom Technique Pada Pasien Chronic Kidney Disease Di Rumah Sakit X - Sintia, Irma Lona; Ananda, Yuanita; Mahathir, Mahathir (Stikes Syedza Saintika Padang, 2025)
CKD patients require treatment that replaces kidney function to sustain life, namely hemodialysis. Hemodialysis requires long and repeated sessions, which can cause physical and psychological problems, such as anxiety disorders. A non-pharmacological intervention that can be implemented to address these problems is spiritual emotional freedom technique (SEFT). SEFT therapy is a type of therapy that combines mind-body interaction by applying pressure to meridian points on the body. The purpose of this research is to describe nursing care for CKD patients undergoing hemodialysis using SEFT therapy to reduce anxiety in patients in the women's internal ward of Dr. M. Djamil Padang General Hospital. The method used is a case study with an evidence-based nursing care approach. The results of implementing SEFT therapy for three days showed a decrease in anxiety scores using the Hamilton Ratting Scale for Anxiety (HARS) questionnaire, from a moderate score of 25 to a mild score of 16. This indicates that SEFT therapy can reduce anxiety in CKD patients undergoing hemodialysis. Nurses are encouraged to implement SEFT therapy as a non-pharmacological intervention to address anxiety disorders in CKD patients undergoing hemodialysis.